Abdominal Incision Injection of Liposomal Bupivacaine and Opioid Use After Laparotomy for Gynecologic Malignancies. Issue 5 (November 2016) - Kalogera, Eleftheria; Bakkum-Gamez, Jamie N.; Weaver, Amy L.; Moriarty, James P.; Borah, Bijan J.; Langstraat, Carrie L.; Jankowski, Christopher J.; Lovely, Jenna K.; Cliby, William A.; Dowdy, Sean C.
Abstract : OBJECTIVE: To investigate opioid use and pain scores associated with incisional injection of liposomal bupivacaine compared with bupivacaine hydrochloride after laparotomy for gynecologic malignancies. METHODS: A retrospective cohort study was conducted to compare abdominal incision infiltration with liposomal bupivacaine with bupivacaine hydrochloride after modification of a pre-existing enhanced recovery pathway. Patients undergoing staging laparotomy or complex cytoreductive surgery under the updated pathway were compared with patients treated under the original pathway (historic controls). Endpoints included cumulative opioid use (primary outcome) in oral morphine equivalents and cumulative pain score. RESULTS: In the complex cytoreductive cohort, median oral morphine equivalents were lower in the liposomal bupivacaine group through 24 hours (30 compared with 53.5 mg, P =.002), 48 hours (37.5 compared with 82.5 mg, P =.005), and the length of stay (62 compared with 100.5 mg, P =.006). Fewer liposomal bupivacaine patients required intravenous rescue opioids (28.9% compared with 55.6%, P <.001) or patient-controlled analgesia (4.1% compared with 33.3%, P <.001). Cumulative pain score was no different between groups through 48 hours (161 compared with 158, P =.69). Postoperative nausea and ileus were less frequent in patients receiving liposomal bupivacaine. Median hospital stay was 5 days in both groups. In the staging laparotomy cohort, cumulative opioids and cumulative pain score were no different between groups (through 48 hours: 162 compared with 161, P =.62; 38 compared with 38, P =.68, respectively). Intravenous rescue opioids (15.3% compared with 28.6%, P =.05) and patient-controlled analgesia (1.4% compared with 8.3%, P =.05) were used less frequently in the liposomal bupivacaine group. Median hospital stay was 4 days in both groups. Despite the higher cost of liposomal bupivacaine, total pharmacy costs did not differ between groups. CONCLUSION: Abdominal incision infiltration with liposomal bupivacaine was associated with less opioid and patient-controlled analgesia use with no change in pain scores compared with bupivacaine hydrochloride after complex cytoreductive surgery for gynecologic malignancies. Improvements were also seen in patients undergoing staging laparotomy. Abstract : Within an enhanced recovery pathway, incisional injection of liposomal bupivacaine is associated with less overall and intravenous opioid use and no change in pain scores compared with bupivacaine hydrochloride.